Tirosin Kinase Inhibitors in Chronic Graft versus Host Disease: From Bench to Bedside - Jacopo Olivieri; Sabrina Coluzzi; Imma Attolico; Attilio Olivieri (The Scientific World Journal)
Chronic Graft Versus Host Disease (cGVHD) is a major complication of allogeneic stem-cell transplantation (SCT). In many inflammatory fibrotic diseases, such as Systemic Scleroderma (SSc) and cGVHD with fibrotic features, an abnormal activation of transforming growth factor (TGFβ) and platelet-derived growth factor receptor (PDGF-R) pathways have been observed. Tyrosin Kinase Inhibitors (TKIs), which are currently used for treatment of patients with Chronic Myeloid Leukemia (CML), share potent antifibrotic and antiinflammatory properties, being powerful dual inhibitors of both PDGF-R and TGFβ pathways. Moreover accumulating in vitro data confirm that TKIs, interacting with the TCR and other signalling molecules, carry potent immunomodulatory effects, being involved in both T-cell and B-cell response. Translation to the clinical setting revealed that treatment with Imatinib can achieve encouraging responses in patients with autoimmune diseases and steroid-refractory cGVHD, showing a favourable toxicity profile. While the exact mechanisms leading to such efficacy are still under investigation, use of TKIs in the context of clinical trials should be promoted, aiming to evaluate the biological changes induced in vivo by TKIs and to assess the long term outcome of these patients. Second-generation TKIs, with more favourable toxicity profile are under evaluation in the same setting.